2021
DOI: 10.1002/vetr.5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of liberal and goal‐directed fluid therapy after small intestinal surgery for strangulating lesions in horses

Abstract: Background: There are few guidelines for the appropriate mode of fluid administration during and after colic surgery, and is challenging to reach the right balance while avoiding overhydration. This study aimed to compare goal-directed fluid therapy (GDFT) and 'liberal' fluid regimens (LFRs) in horses undergoing small intestinal surgery. Methods: Eighteen horses subjected to small intestinal surgery were matched according to the surgical lesion, type of anastomosis, length of resection, and duration of clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Post-operative treatments are often expensive, and it is essential to reduce the cost of colic surgery through a more selective approach to drug use and a greater emphasis on preventing complications [ 2 , 43 ]. A study by Giusto and colleagues showed that “goal directed” fluid administration is not associated with higher postoperative complications than standard rates of administration, and it has the advantage of being less expensive and reducing hospitalization time [ 44 ]. Crystalloid administration influenced the outcome in this study and although there are no studies showing the effect of overhydration on the outcome in horses, the results of our study confirm the need to use a goal directed fluid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Post-operative treatments are often expensive, and it is essential to reduce the cost of colic surgery through a more selective approach to drug use and a greater emphasis on preventing complications [ 2 , 43 ]. A study by Giusto and colleagues showed that “goal directed” fluid administration is not associated with higher postoperative complications than standard rates of administration, and it has the advantage of being less expensive and reducing hospitalization time [ 44 ]. Crystalloid administration influenced the outcome in this study and although there are no studies showing the effect of overhydration on the outcome in horses, the results of our study confirm the need to use a goal directed fluid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This study by Gessica Giusto and co‐workers in Italy compared goal‐directed fluid therapy (GDFT) and 'liberal' fluid regimens (LFRs) in horses undergoing small intestinal surgery .…”
Section: Fluid Therapy After Colic Surgerymentioning
confidence: 99%
“…25 Such fluids in low volumes could replace water needs in less critical postoperative colic cases more effectively than replacement fluids that are too high in sodium. 20,22,24 In Giusto and colleagues' study, 1 horses were assigned to undergo either liberal (LFR) or goaldirected (GDFT) approaches to fluid therapy. For at least 24 hours after surgery, the LFR group received intravenous fluids at 2 ml/kg/h (ie, Fluid therapy for horses is usually delivered by intravenous infusion from 5 litre bags.…”
Section: What You Need To Knowmentioning
confidence: 99%
“…In Giusto and colleagues’ study, 1 horses were assigned to undergo either liberal (LFR) or goal‐directed (GDFT) approaches to fluid therapy. For at least 24 hours after surgery, the LFR group received intravenous fluids at 2 ml/kg/h (ie, 80 per cent of the maintenance rate for a fed horse), combined with sufficient additional fluids to offset losses.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation